Cyper-coconut yoghurt: preparation, compositional and organoleptic qualities - Belewu; M.A; Belewu; K.Y; Bamidele; R.A. (Global Journal of Food and Agribusiness Management, 2010)
In this study the possibility of using various plant milk sources in the making of yoghurt was investigated in a completely randomized design model. Yoghurts were made using Cow milk (T1), Coconut milk (T2) , Tigernut milk (T3), 50% Tigernut milk + 50% Coconut milk (T4) 50% Tigernut + 50% Soybean milk (T5) and 50% Tigernut + 50% Cow milk (T6). The various yoghurt samples were analyzed for chemical composition and sensory qualities were tested. The sensory quality was determined using a nine point hedonic scale. It was observed that the samples of yoghurt from Tigernut milk (T3) and 50% Tigernut +50% Soybean milk (T5) were higher in crude protein and total solids while the titrable acidity was. 0.5 in Tigernut milk yoghurt (T3). The overall sensory score was 5.0 for all types of yoghurts included in this study. The yoghurt made from 50% Tigernut milk + 50% Cow milk yoghurt (T6) had similar sensory qualities compared to yoghurt from other sources. The higher chemical composition, cost per kg of each yoghurt samples and sensory scores of yoghurt prepared from Tigernut milk and Coconut milk sources as well as their potential therapeutic effects may well be encouraging for the Nigerian dairy industry.